Cartilage hair hypoplasia: Characteristics and orthopaedic manifestations. (April 2015) - Riley, Patrick; Weiner, Dennis S.; Leighley, Bonnie; Jonah, David; Morton, D. Holmes; Strauss, Kevin A.; Bober, Michael B.; Dicintio, Martin S.
Purpose: Cartilage hair hypoplasia (CHH) is a rare metaphyseal chondrodysplasia characterized by short stature and short limbs, found primarily in Amish and Finnish populations. Cartilage hair hypoplasia is caused by mutations in the RMRP gene located on chromosome 9p13.3. The disorder has several characteristic orthopaedic manifestations, including joint laxity, limited elbow extension, ankle varus, and genu varum. Immunodeficiency is of concern in most cases. Although patients exhibit orthopaedic problems, the orthopaedic literature on CHH patients is scant at best. The objective of this study was to characterize the orthopaedic manifestations of CHH based on the authors' unique access to the largest collection of CHH patients ever reported. Methods: The authors examined charts and/or radiographs in 135 cases of CHH. We analyzed the orthopaedic manifestations to better characterize and further understand the orthopaedic surgeon's role in this disorder. In addition to describing the clinical characteristics, we report on our surgical experience in caring for CHH patients. Results: Genu varum, with or without knee pain, is the most common reason a patient with CHH will seek orthopaedic consultation. Of the cases reviewed, 32 patients had undergone surgery, most commonly to correct genu varum. Conclusion: This paper characterizes the orthopaedic manifestations of CHH. Characterizing this condition in the orthopaedic literature will likely assist orthopaedic surgeons in establishing a correct diagnosis and appreciating the orthopaedic manifestations. It is important that the accompanying medical conditions are appreciated and evaluated.